Administrative Sanctions for Hospitals Which Grant Permission for Forced Taking the Corpse of Suspect Covid-19 Patients (Medico Legal Update, 2021)
This study is intended to analyze the bodies of suspect Covid-19 patients in the Covid-19 Protocol and theresponsibilities of the perpetrators of forcibly taking the bodies of Suspect or Probable patients in criminallaw. This research is a juridical normative research, which is focused on studying the application of normsin positive law by combining legal materials which are secondary and primary legal materials. The approachtaken is a statue and a conceptual approach. Based on the results of this study it can be concluded that thepatient’s body is a suspect Covid-19 body, it must be treated like the Covid-19 body until there is a resultfrom the swab test to fulfill the rights of the body, the responsibility of the perpetrator of forced taking of thesuspect / probable patient’s body in criminal law, among others sentenced to a criminal sentence on the basisof Article 5 of Law No. 4 of 1984 concerning Outbreaks of Infectious Diseases with the threat of one yearin prison or a fine of up to Rp. 100,000,000 (One Hundred Million Rupiah).